Planisphere des Croynces Religieuses et des Missions Chretiennes par Valerien Groffier - Groffier, Valerien | Wuhrer, L. (NC, 1883)
Zoomable full resolution image available at davidrumsey.com . This image 12043.000 is a part of image group 12043.000 . Black slip cover. Map cut into 18 panels and mounted on linen with spaces between panels for folding.
Source a verifier sur Internet Archive
Keywords: paris